THE ESTABLISHMENT OF ISLAMIC BANKING LAW IN POLITICAL PERSPECTIVE - Hejazziey, Djawahir (al-'adalah, 2015)
Abstrak: Pembentukan UU Perbankan Islam dalam Perspektif Politik. Artikel ini mendiskusikan sejarah berdirinya perbankan syariah di Indonesia. Pada awalnya, di masa Orde Baru, hubungan antara umat Islam dengan pemerintah diliputi dengan kecurigaan dan prasangka bahwa setiap yang berbau Islam dianggap upaya untuk merealisasikan Piagam Jakarta atau untuk mendirikan negara Islam. Tetapi kemudian, ketika Indonesia mengalami kegoncangan ekonomi yang begitu hebat dan diikuti dengan perubahan dalam struktur politik/pemerintahan, gagasan umat Islam Indonesia untuk mendirikan Bank Syariah akhirnya dapat diwujudkan. Keberhasilan pembentukan lembaga perbankan syari’ah ini, berdasarkan data yang penulis peroleh, tidak terlepas dari situasi politik yang melingkupinya. Abstract: The Ratification of the Islamic Banking Act in Political Perspective. This article discusses the history of the formation of Islamic banking in Indonesia. At first, in the New Order era, the relationship between Muslims and the government was filled with suspicion and prejudice that every activities related to Islam was considered as an attempt to actualize the Jakarta Charter or to establish an Islamic state. However, when Indonesia experienced economic hardship followed by changes in the structure of politics/government, the idea of Indonesian Muslims to establish shariah bank can ultimately be realized. The success of the establishment of the shariah banking institutions, in many ways, can not be separated from the then political circumstances.